Ardis da palavra cerceada: o discurso tático: processos de significação em romances portugueses da década de 60 - Monfardini, Adriana (2011)
In this study, we examine ways of production and dissemination of meanings in two portuguese novels of the 60s Maina Mendes (1969), by Maria Velho da Costa, and A noite e o riso (1969), by Nuno Bragança. Produced in a dictatorial period, these works point to this context, although not mentioning it directly, acting as a delicate instrument of combat. To this end, these novels utilize resources that rely on different processes of signification, through which they reveal, in a sinuous and not rarely cynical way, a reality that could not be referred to and much less criticized explicitly. The analysis carried out focuses on these processes in order to observe how they act as triggers of a subtextual level of political nuance, helping to configure what we call tactical discourse . The proposed analysis is supported by literary and linguistic studies, as well as some theoretical formulations form the social science.